Australian sport: the pathway to success (Commonwealth of Australia, 2010)
The Australian Government understands the importance of sport to our communities and to our nation. We have made the single biggest investment in community sporting infrastructure that this nation has ever seen, delivering $300 million to sport under the $1 billion Regional and Local Community Infrastructure Program (RLCIP). With the release of Australian Sport: The Pathway to Success we are backing this up with an injection of $195 million in new funding to sport, the biggest increase in sports funding in Australia`s history, as well as a comprehensive plan of reform to benefit the health of our community and of our sports sector. Australian Sport: The Pathway to Success takes a holistic approach to our sporting system that is aimed at strengthening sport as a whole. Through renewed focus and strategy, enhanced partnerships across tiers of government, a close co-operative approach with our sporting organisations and the biggest increase to sports funding in Australia`s history, Australian Sport: The Pathway to Success maps the course for increased opportunities for Australians to participate in sport and activity - and Australia`s continued sporting excellence.